Leaf morphology and anatomy of 7 varieties of ficus deltoidea (Moraceae) - Nur Fatihah, Hasan Nudin; Abd Manaf, Ali; Nashriyah, Mat (2014)
The extreme morphological variations and unclear boundaries between varieties creates misleading identification of Ficus deltoidea Jack (Moraceae) varieties. This has encouraged many taxonomists and botanists to study the variation within F. deltoidea. Thus, correct identification of F. deltoidea varieties is important as several morphological and anatomical characters are variety-specific. The present study aims to evaluate the morphology and anatomy of leaf in seven varieties of F. deltoidea, namely var. deltoidea, var. angustifolia, var. trengganuensis, var. bilobata, var. intermedia, var. kunstleri and var. motleyana. It is also targeted to contribute to the identification of the varieties based on the matured leaf characters. The results have revealed varying morphological characters in the type of leaf shape, size, surface texture, margin, midrib dichotomous and petiole length. Moreover, variation in anatomical characters concerning structures of the lamina, leaf epidermis and midrib has also been demonstrated.